Fuzzy logic based MPPT controller for high conversion ratio quadratic boost converter - Ozdemir, Saban; Altin, Necmi; Sefa, Ibrahim (International journal of hydrogen energy, 2017)
In this study, a maximum power point tracking DC–DC quadratic boost converter for high conversion ratio required applications is proposed. The proposed system consists of a quadratic boost converter with high step-up ratio and fuzzy logic based maximum power point tracking controller. The fuzzy logic based maximum power point tracking algorithm is used to generate the converter reference signal, and the change in PV power and the change in PV voltage are selected as fuzzy variables. Determined membership functions and fuzzy rules which are design to track the maximum power point of the PV system generates the output signal of the fuzzy logic controller's output. It is seen from MATLAB/Simulink simulation and experimental results that the quadratic boost converter provides high step-up function with robustness and stability. In addition, this process is achieved with low duty cycle ratio when compared to the traditional boost converter. Furthermore, simulation and experimental results have validated that the proposed system has fast response, and it is suitable for rapidly changing atmospheric conditions. The steady state maximum power point tracking efficiency of the proposed system is obtained as 99.10%. Besides, the output power oscillation of the converter, which is a major problem of the maximum power point trackers, is also reduced. •A MPPT DC–DC quadratic boost converter is proposed for the high conversion ratio applications.•The fuzzy logic based control algorithm is used to track the maximum power point of the PV system.•The steady state MPPT efficiency of the proposed system is obtained as 99.10%.•The proposed system is suitable for rapidly changing atmospheric conditions.